2021
DOI: 10.1111/bcpt.13613
|View full text |Cite
|
Sign up to set email alerts
|

Current and emerging pharmacological targets for medical expulsive therapy

Abstract: The primary goals of medical expulsive therapy are to increase the rate of stone expulsion along the ureter to avoid ureteral obstruction and reduce ureteral colic and thus avoid the need for surgical and more invasive interventions. This review focussed on the findings from in vivo and in vitro animal and human studies that have investigated the pharmacological mechanisms controlling ureteral motility and their translation to current and potentially new clinically used drugs for increasing the rate of stone e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The frequency of ureteric peristalsis is enhanced by stimulation of alpha 1 AR precisely in the ureter. Tamsulosin has been in use for the treatment of lower uretic calculi for patients that have stones less than 10mm in size [13][14] . Previous studies have shown that it improves the rate of stones explosion, and the rate is increased with less pain and less need of analgesics 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of ureteric peristalsis is enhanced by stimulation of alpha 1 AR precisely in the ureter. Tamsulosin has been in use for the treatment of lower uretic calculi for patients that have stones less than 10mm in size [13][14] . Previous studies have shown that it improves the rate of stones explosion, and the rate is increased with less pain and less need of analgesics 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Chua et al 4 similarly consider a common side-effect to chemotherapy, namely peripheral neuropathy, focusing on microtubule-targeting agents and how translational genetic studies covering both genome-wide association studies and functional genomic studies using pluripotent stem cells will bring us forward in our understanding of chemotherapy-induced neuropathy. Lim et al 5 review pharmacological agents of current or potential future use as medical expulsive therapy in urolithiasis, leveraging both in vitro and in vivo studies to provide recommendations for candidate drug classes for further clinical investigation. Eisenmann et al 6 review how pharmacokinetic knowledge can be used to improve the oral bioavailability of anticancer drugs by deploying intentional drug-drug interactions.…”
Section: Translational Pharmacology: Closing the Mechanistic Gapmentioning
confidence: 99%
“…It has been established that mirabegron is safe, efficient, and well-tolerated. In almost all trials, it produced outcomes that were comparable to placebo in terms of the prevalence of dry mouth (3) . The bladder's detrusor smooth muscle relaxes as a result of the beta-3 adrenergic receptor agonist mirabegron, which also improves bladder capacity.…”
Section: Introductionmentioning
confidence: 97%